A Metabolic Change towards Fermentation Drives Cancer Cachexia in Myotubes - Michele Mannelli; Tania Gamberi; Francesca Magherini; Tania Fiaschi (Biomedicines, 2021)
Cachexia is a disorder associated with several pathologies, including cancer. In this paper, we describe how cachexia is induced in myotubes by a metabolic shift towards fermentation, and the block of this metabolic modification prevents the onset of the cachectic phenotype. Cachectic myotubes, obtained by the treatment with conditioned medium from murine colon carcinoma cells CT26, show increased glucose uptake, decreased oxygen consumption, altered mitochondria, and increased lactate production. Interestingly, the block of glycolysis by 2-deoxy-glucose or lactate dehydrogenase inhibition by oxamate prevents the induction of cachexia, thus suggesting that this metabolic change is greatly involved in cachexia activation. The treatment with 2-deoxy-glucose or oxamate induces positive effects also in mitochondria, where mitochondrial membrane potential and pyruvate dehydrogenase activity became similar to control myotubes. Moreover, in myotubes treated with interleukin-6, cachectic phenotype is associated with a fermentative metabolism, and the inhibition of lactate dehydrogenase by oxamate prevents cachectic features. The same results have been achieved by treating myotubes with conditioned media from human colon HCT116 and human pancreatic MIAPaCa-2 cancer cell lines, thus showing that what has been observed with murine-conditioned media is a wide phenomenon. These findings demonstrate that cachexia induction in myotubes is linked with a metabolic shift towards fermentation, and inhibition of lactate formation impedes cachexia and highlights lactate dehydrogenase as a possible new tool for counteracting the onset of this pathology.